-3x-5=-2x-4

Simple and best practice solution for -3x-5=-2x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-5=-2x-4 equation:


Simplifying
-3x + -5 = -2x + -4

Reorder the terms:
-5 + -3x = -2x + -4

Reorder the terms:
-5 + -3x = -4 + -2x

Solving
-5 + -3x = -4 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-5 + -3x + 2x = -4 + -2x + 2x

Combine like terms: -3x + 2x = -1x
-5 + -1x = -4 + -2x + 2x

Combine like terms: -2x + 2x = 0
-5 + -1x = -4 + 0
-5 + -1x = -4

Add '5' to each side of the equation.
-5 + 5 + -1x = -4 + 5

Combine like terms: -5 + 5 = 0
0 + -1x = -4 + 5
-1x = -4 + 5

Combine like terms: -4 + 5 = 1
-1x = 1

Divide each side by '-1'.
x = -1

Simplifying
x = -1

See similar equations:

| 6+9(7-2)= | | 8+t=5 | | 2y/3-y/4=15 | | -2w=4(w-3) | | -26-6n=4(7n+8) | | (2x^2)+(8x)+(2y^2)=0 | | 3.9v+2.4=0.9v+5.4 | | 8-6t=-16 | | 96=L*w-4 | | 3k+(2k+5)= | | t-ma=w | | ((3t-8)/(10t-3))=0 | | (2x^2)+(8x^2)+(2y^2)=0 | | 3(5x-5)=8x+13 | | 175=6x+8x | | 4.32+4m=6.48 | | -3x+4x=8-x | | 0=6v-9 | | 6.3x-4=2.6x-3 | | -23+4m=57 | | 23(j+2)=4j | | 9.4=d+5.6 | | 8j-5=11 | | 2(4x-1)=3(x+3)-2 | | 6zy-2z= | | (y+5)+1=3y | | 2x^0= | | 23v-40=23 | | -4j+8=-32 | | (3x)-20=43 | | 1/3x-y=7 | | y=2.6x-4.2 |

Equations solver categories